Indonesia and the Global South: A Constructivist Approach to Diplomatic Leadership in a Multipolar World Order - Heriamsal, Krisman (Kementerian Luar Negeri Republik Indonesia, 2025)
The global power structure has shifted from a unipolar system to multipolarity, marked by the emergence of new powers such as China and Russia and the strengthening of regional cooperation. In this context, the role of Global South countries is becoming increasingly important in shaping a new, more inclusive world order. This study highlights how Indonesia constructs and projects its identity and leadership as a representation of the Global South in the multipolar era. The purpose of the study is to analyze the construction of Indonesia's identity and the diplomatic practices used in forums such as the G20 and BRICS to advocate the interests of developing countries. This study uses a qualitative method with an interpretive approach, based on an analysis of official speeches, diplomatic documents, and scientific literature. Theoretically, this study is based on the constructivism of international relations, especially Alexander Wendt's ideas about the importance of identity and norms in shaping state interests. The results show that Indonesia actively uses normative diplomacy, historical narratives, and multilateral engagement to strengthen its position as a leader of the Global South and encourage reforms to a more just and equal global order